Does washing medical devices before and after use decrease bacterial contamination?: An in vitro study - Nai, Gisele Alborghetti; Medina, Denis Aloísio Lopes; Martelli, Cesar Alberto Talavera; de Oliveira, Mayla Silva Cayres; Portelinha, Maria Júlia Schadeck; Henriques, Bruno Carvalho; Caldeira, Isadora Delfino; Almeida, Mércia de Carvalho; Eller, Lizziane Kretli Winkelstroter; Neto, Fausto Viterbo de Oliveira; Marques, Mariângela Esther Alencar [UNESP] (Wolters Kluwer, 2021)
ABSTRACT: Surface treatment of medical devices may be a way of avoiding the need for replacement of these devices and the comorbidities associated with infection. The aim of this study was to evaluate whether pre- and postcontamination washing of 2 prostheses with different textures can decrease bacterial contamination.The following microorganisms were evaluated: Staphylococcus aureus, Staphylococcus epidermidis, Proteus mirabilis and Enterococcus faecalis. Silicone and expanded polytetrafluoroethylene vascular prostheses were used and divided into 3 groups: prostheses contaminated; prostheses contaminated and treated before contamination; and prostheses contaminated and treated after contamination. Treatments were performed with antibiotic solution, chlorhexidine and lidocaine. After one week of incubation, the prostheses were sown in culture medium, which was incubated for 48 hours. The area of colony formation was evaluated by fractal dimension, an image analysis tool.The antibiotic solution inhibited the growth of S epidermidis and chlorhexidine decrease in 53% the colonization density for S aureus in for both prostheses in the pre-washing. In postcontamination washing, the antibiotic solution inhibited the growth of all bacteria evaluated; there was a 60% decrease in the colonization density of S aureus and absence of colonization for E faecalis with chlorhexidine; and lidocaine inhibited the growth of S aureus in both prostheses.Antibiotic solution showed the highest efficiency in inhibiting bacterial growth, especially for S epidermidis, in both washings. Lidocaine was able to reduce colonization by S aureus in post-contamination washing, showing that it can be used as an alternative adjuvant treatment in these cases.